Local injection of Platelet Rich Plasma for Plantar Fasciitis - Phadke, Vishwas Sharad; Antrolikar, Vaibhav Vinayak; Allamwar, Ajaykumar Ramlu (Asian Journal of Medical Sciences, 2021)
Background: Plantar fasciitis can be defined as inflammation at the insertion of plantar fascia and is thought most commonly due to overuse injury. It usually presents as sharp shooting heel pain which is worse in the morning. The location of pain is usually plantar surface of the foot and pain may radiate proximally in long standing and severe cases. In mild cases of plantar fasciitis non steroidal anti-inflammatory drugs and activity modification may be sufficient. Severe cases may require interventions such as night splints and orthotic devices which works by reducing loading of plantar fascia. Recently local injection of autologous platelet rich plasma is used by many researchers with promising results. Aims and Objectives: This prospective cohort study was undertaken to analyze the functional and clinical outcome in patients with plantar fasciitis who were treated by autologous injection of platelet rich plasma. Materials and Methods: This was a prospective cohort study conducted in department of orthopedics of a tertiary care medical college located in an urban area. The patients diagnosed to be having plantar fasciitis were included in this study on the basis of a predefined inclusion and exclusion criteria. Patients were assessed for severity of pain by the Visual Analogue Score for pain and American orthopedic foot and ankle score (AOFAS). A VAS score of 0-3 was taken as pain relief and VAS score of 4-10 was considered as no pain relief. Whereas AOFAS scores of 90-100, 80-89, 60-79 and less than 60 were taken as excellent, good, fair and poor outcome respectively. All patients were treated by local injection of autologous platelet rich plasma. The patients were followed up at 4 weeks, 8 weeks and 12 weeks. During follow up visits the pain relief was assessed by VAS and AOFAS scores. For statistical purposed SSPS 21.0 software was used and p value less than 0.05 was taken as statistically significant. Results: A total of 60 patients were included in this study out of which there were 22 (36.67%) males and 38 (63.33%) females with a M:F ratio of 1:1.72. The most common affected age group was between the age of 41-50 years (35%) followed by 51-60 years (21.67%) and 31-40 years (20%). Twenty-seven (45%) patients were either overweight or obese. A statistically significant reduction in pain was documented at the time of follow up of 4 weeks. At the end of 12 weeks 58 (96.67%) patients experienced significant pain relief and only 2 (3.33%) patients had significant pain. Also, there was statistically significant difference between AOFAS scores at the time of presentation and at 4 weeks, 8 weeks and 12 weeks follow up visits. Conclusion: Injection of autologous platelet rich plasma for chronic plantar fasciitis is found to have promising results in terms of pain relief (reduced VAS score) and functional outcome (Improvement in AOFAS score).